2002
DOI: 10.1038/sj.ejhg.5200766
|View full text |Cite
|
Sign up to set email alerts
|

A detailed transcriptional map of the chromosome 12p12 tumour suppressor locus

Abstract: Loss of heterozygosity of the short arm of chromosome 12 is a frequent event in a wide range of haematological malignancies and solid tumours. In previous studies, the shortest commonly deleted region was delimited to a 750-kb interval, defined by the markers D12S89 and D12S358, in pre-B acute lymphoblastic leukaemia patients, suggesting the presence of a tumour suppressor locus. Here we report the construction of a transcriptional map that integrates the data obtained by genomic sequence analysis, EST databas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
36
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 41 publications
2
36
0
Order By: Relevance
“…While deletion analysis at different tumor sites should be approached with caution, it is interesting that these 3 (BCLG, FLJ10298, DUSP16) also lie within the previously reported leukemia minimal region of deletion. 22 Previous studies confirmed our finding that all 3 genes are expressed in normal prostate, 21 which makes them attractive candidates for a 12p12-13 prostate cancer tumor-suppressor gene (Fig. 2).…”
Section: Expression Analysis Of Candidate Genes Within the Minimal Resupporting
confidence: 80%
See 4 more Smart Citations
“…While deletion analysis at different tumor sites should be approached with caution, it is interesting that these 3 (BCLG, FLJ10298, DUSP16) also lie within the previously reported leukemia minimal region of deletion. 22 Previous studies confirmed our finding that all 3 genes are expressed in normal prostate, 21 which makes them attractive candidates for a 12p12-13 prostate cancer tumor-suppressor gene (Fig. 2).…”
Section: Expression Analysis Of Candidate Genes Within the Minimal Resupporting
confidence: 80%
“…Additional exons have been identified, and it has been hypothesized that additional isoforms may exist; however, they also appear to be expressed only in the testis. 21 Real-time-PCR demonstrated a striking decrease in transcript levels of BCLG in both clinical and cultured prostate carcinomas (Tables III, IV, Fig. 3).…”
Section: Candidate Genesmentioning
confidence: 93%
See 3 more Smart Citations